Pemanfaatan Produk Rancangan Mahasiswa (Media Diorama) STIT Al Hilal Sigli di MIN 18 Pidie - Cut Keumalawati; Gusti Handayani; Junaidah; Nasri Diana (PT. Riset Mandiri Nusantara, 2025)
Instructional media plays a crucial role in conveying educational messages, capturing students’ attention, and enhancing their learning motivation. One effective medium to support the learning process is the use of diorama-based media. This community service activity aims to: (1) assist in clarifying the presentation of learning materials to improve students’ knowledge and understanding through the use of diorama media designed by students of the PGMI Program at Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli; and (2) facilitate collaborative learning between students of MIN 18 Pidie and university students through inter-institutional cooperation. This activity employed a qualitative descriptive method with a participatory approach. The results indicated that the presentation of the diorama media was carried out smoothly and received positive responses from the students. As a combination of visual elements and three-dimensional forms, the diorama effectively represents subject matter in a realistic way, enhances learning motivation, and provides students with direct learning experiences. In conclusion, diorama media not only offers in-depth visualization of the subject matter but also improves students’ memory retention through direct engagement with attractive and contextual visual media.